2014
DOI: 10.3892/or.2014.3555
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of epigallocatechin-3-gallate in human esophageal squamous cell carcinoma in vitro and in vivo

Abstract: Abstract. Epigallocatechin-3-gallate (EGCG), the major polyphenol of green tea, has been shown to inhibit proliferation in various types of tumors. However, few studies concerning the role and mechanism of EGCG in esophageal squamous cell carcinoma are available. Therefore, the antitumor mechanism of EGCG needs to be investigated. The present study aimed to examine the antitumor effect of EGCG on the human esophageal squamous cell carcinoma cell lines, Eca-109 and Te-1, in vitro and in vivo. Cell viability was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…In addition, these polyphenols modulate the functions of various cancer-related signaling molecules. For example, the function and expression of vascular endothelial growth factor (VEGF), which is a strong stimulator of angiogenesis, are mediated by GTPs in oral cancer and esophageal squamous cell carcinoma [ 14 , 29 ]. Furthermore, in these malignancies, cyclin D1, which is a cell cycle regulator, and caspase-3, which is an important determinant for apoptosis, are associated with GTPs [ 14 , 29 ].…”
Section: Anticancer Effects Of Green Tea Polyphenolsmentioning
confidence: 99%
“…In addition, these polyphenols modulate the functions of various cancer-related signaling molecules. For example, the function and expression of vascular endothelial growth factor (VEGF), which is a strong stimulator of angiogenesis, are mediated by GTPs in oral cancer and esophageal squamous cell carcinoma [ 14 , 29 ]. Furthermore, in these malignancies, cyclin D1, which is a cell cycle regulator, and caspase-3, which is an important determinant for apoptosis, are associated with GTPs [ 14 , 29 ].…”
Section: Anticancer Effects Of Green Tea Polyphenolsmentioning
confidence: 99%
“…sinensis . Epidemiological studies and murine models have identified promising results for green tea and its constituents in reducing the risk of cancer in different organs 8 ā€“ 11 . Green tea inhibited tumor growth in xenograft models by suppressing the metastasis on metastasis-specific mouse mammary carcinoma 4T1 cells 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Green tea inhibited tumor growth in xenograft models by suppressing the metastasis on metastasis-specific mouse mammary carcinoma 4T1 cells 12 . In addition, epigallocatechin-3-gallate (EGCG), the major polyphenol of green tea, has been shown to inhibit proliferation and induce apoptosis through caspase-3 activation and to decrease VEGF expression in esophageal squamous cell carcinoma in vitro and in vivo 8 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…BaP promoted significant G2/M arrest, and it is widely accepted that BaP exposure can cause DNA damage, so G2/M arrest allows for DNA repair prior to mitosis to prevent the propagation of mutated cells . Either G1 or G2/M arrest induction upon EGCG treatment has been observed in esophageal and lung cancer cell lines. Cells coā€treated with BaP and EGCG had a significant induction of ROS compared with the BaPā€treated cells after 2, 4, and 8 h. Hwang et al found that colon cancer cells treated with EGCG for 6 h induced ROS formation, so the same phenomena could have occurred in this study .…”
Section: Discussionmentioning
confidence: 99%